2021
DOI: 10.21203/rs.3.rs-291426/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Fiscal Decentralization and Green Innovation mitigate the environmental pollution with the help of Institutional governance? Evidence from Asian Countries using novel (MMQR)

Abstract: This research aims to examine the influence of fiscal decentralization and green innovation on CO2 emission with the help of institutional governance. Heterogeneous panel estimations and cross-sectional dependence approaches have been applied to remove the coefficient magnitude differences of 48 countries spanning from the year 1998 to 2018. The results of the novel methodology “Method of Moments Quantile Regression” (MMQR) shows that fiscal decentralization, green innovation, institutional governance, and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Energy-saving and pollution-mitigation programs are used by city authorities in highly decentralized areas to guarantee that their energy-saving and carbon-neutrality objectives are accomplished. This empirical evidence is also consistent with Rani’s ( 2021 ) findings that fiscal decentralization aids Asian countries in reducing pollution. In this light, the authors argued that fiscal decentralization might be increased through human capital and green innovation in order to attain ecological sustainability in Asian block examined.…”
Section: Empirical Results and Their Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Energy-saving and pollution-mitigation programs are used by city authorities in highly decentralized areas to guarantee that their energy-saving and carbon-neutrality objectives are accomplished. This empirical evidence is also consistent with Rani’s ( 2021 ) findings that fiscal decentralization aids Asian countries in reducing pollution. In this light, the authors argued that fiscal decentralization might be increased through human capital and green innovation in order to attain ecological sustainability in Asian block examined.…”
Section: Empirical Results and Their Discussionsupporting
confidence: 90%
“…However, their empirical findings have produced far more heat than light, resulting in significant discrepancies in the evidence across different methodologies and nations tested. While many studies have found that fiscal decentralization improves environmental quality (Xu 2022 ; Tufail et al 2021 ; Rani 2021 ), others have found that fiscal decentralization worsens it (Yang et al 2021a ; Xiao-Sheng et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tufail et al (2021) used panel data from seven highly fiscally decentralized OECD countries to investigate the effect of fiscal decentralization on CO 2 emissions and observed that fiscal decentralization improves the environment for the OECD group. Similarly, Rani (2021) utilized the novel Method of Moments Quantile Regression approach and showed that fiscal decentralization helped to minimize environmental pollution in Asian nations from 1998 to 2018. In addition, Jain et al (2021) explored the dynamic influence of fiscal decentralization on environmental quality for nine Asian nations from 1984 to 2017.…”
Section: Fiscal Decentralization-environmental Quality Nexusmentioning
confidence: 99%
“…However, limiting CO 2 emissions would result in lower output, which would impede economic growth. The reason is that this case is linked to energy usage, which is crucial for economic development (Jain et al 2021;Li et al 2021a, b, c;Rani 2021). Thus, following or implementing measures that are intended to curb rising temperatures directly is exceedingly difficult for these nations.…”
Section: Introductionmentioning
confidence: 99%